ANALISIS FAKTOR DETERMINAN YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL TRIMESTER III DI PUSKESMAS MPUNDA - Febriyanti, Maya (Jurnal Ilmiah Bidan (JIB), 2023)
The incidence of anemia in Indonesia is estimated to occur in 41 cases of anemia per day and 20 womendie. The incidence of anemia in pregnant women at the Mpunda Health Center increased from 122 cases in2018 to 135 cases in 2019 and 179 cases in 2020. This study aims to analyze the determinant factorsassociated with the incidence of anemia in third trimester pregnant women at the Mpunda Health Center.This research analytic descriptive analytic with cross-sectional approach. The population is 52 pregnantwomen in the third trimester of the March-August 2021 period with the sample technique using totalsampling. Data collecting using questionnaires and observations of MCH books and measurements withdigital Hb. The statistical tests used were chi square and backward logistic regression. The results of studyshowed that the variables that were significantly related to the incidence of anemia in pregnancy (p <0.05)were. education, knowledge, consumption pattern of Fe tablets, husband's support and culture. Thedominant variable related to the incidence of pregnant women in the third trimester is the consumptionpattern of Fe tablets. Pregnant women who consume Fe tablets irregularly have a significant 11.6 timeschance of suffering from anemia compared to those who consume regularly (POR = 11.684; 95% CI: 1.311-104.12). Health workers are expected to improve services for pregnant women, especially monitoring theconsumption of Fe tablets